DİKGEN FREKANS BÖLMELİ ÇOKLU ERİŞİM SİSTEMLERİNDE KANAL KESTİRİMİ VE PERFORMANS ANALİZİ - ATİLA, ORHAN (Fırat Üniveristesi, 2016)
Teknolojinin hızla gelişmesine paralel olarak bilgiye her an her yerden ulaşabilme ihtiyacı her geçen gün önem kazanmakta, bununla beraber kablosuz haberleşmede ki veri iletim oranı ve veri iletim hızı talebi de günden güne artış göstermektedir. Bu ihtiyaçları karşılayabilmek için haberleşme sistemlerinde kullanılan tek taşıyıcılı modülasyon sistemleri yerini günümüzde artık çok taşıyıcılı modülasyon sistemlerine bırakmıştır. OFDM (Dikgen Frekans Bölmeli Çoklu Erişim) mevcut frekans spektrumunu alt kanallara bölerek paralel iletim sağlamakta ve veri hızını önemli ölçüde arttırmaktadır. Ayrıca alt kanalların birbirine dikgen olması %50'ye varan bir bant genişliği tasarrufu sağlamaktadır. OFDM' in bu olumlu özellikleri 802.11 (WiFi) ve 802.16 (WiMAX) gibi yeni nesil haberleşme standartlarında yerini almasını sağlamıştır. Dolayısıyla son zamanlarda OFDM sisteminin çoklu yol zayıflamalı frekans seçici kanallarda performansını değerlendiren çalışmalar ağırlık kazanmıştır. Kanal yapılarının zamanla rasgele değişen frekans cevabının kestirilerek tasarlandığı denkleştirici yapıları da bu konuda araştırma konusu olan diğer önemli bir bölümü oluşturmaktadır. Özellikle kanalların semboller arası girişime (ISI) neden olan etkilerine karşı dayanıklılık kazandırmak için yeni yöntemler araştırılmaktadır. Bu yöntemleri değerlendirirken direk görüşlü (LOS) ve direk görüşü olmayan (NLOS) istatistiksel farklı kanal modelleri kullanılarak, kanal parametrelerine göre bit hata oranları (BER) incelenmektedir. Bu çalışmada OFDM tekniğinin kullanımında örnek bir sistem olması ve uygulama alanı bulması nedeniyle 802.11 kablosuz haberleşme standartları incelenmiş, serpiştirici ve kanal kodlama yapıları ele alınmıştır. Rayleigh, Rician, AWGN kanal modelleri üzerinde OFDM sistem yapısı benzetimi gerçeklenmiş ve performansı değerlendirilmiştir. Kanal kestirimi için kullanılan LS, MMSE, LRMMSE algoritmaları karşılaştırılmıştır. Anahtar Kelimeler: OFDM, WiFi, WiMAX, ISI, LOS, NLOS, BER, MMSE, LS, LRMMSE

CHANNEL ESTIMATION AND PERFORMANCE ANALYSIS IN ORTHOGONAL FREQUENCY DIVISION MULTIPLE ACCESS SYSTEM Parallel to the rapid growth of technology the need for reaching information in anywhere or at any moment is gaining importance day by day, and with this situation the rate of transmitting data and the speed demand of transmitting data in wireless communication are growing day by day too. In order to provide these needs, single carrier modulation systems used in communication systems give their place to the multi carrier modulation systems. OFDM (Orthogonal Frequency Division Multiple Acces) provides parallel transmission and increases the data speed significantly by dividing the available frequency spectrum into the sub-channels. Furthermore,sub-channels orthogonality provides a bandwidth saving up to fifty percent.These positive features of OFDM provide it to have a place in new generation communication standarts such as 802.11 (WiFi) and 802.16 (WIMAX).Therefore the studies which evaluate the performance in inter-symbol frequency selective channels of OFDM system have gained importance recently.Equalizer structures which are designed by estimating the frequency response of channel structures changing randomly in time is an important research subject in this section.Particularly,the new methods are searched in order to provide resistance against the effects causing the inter-symbol interference(ISI) of channels.When evaluating these methods,bit error rates(BER) are examined according to the channel parametres by using the statistical different models of line of sight(LOS) and no line of sight(NLOS) channels. For being a model system in the use of OFDM technique and finding usage in implementation fields, 802.11 and 802.16 wireless communication systems are analyzed, interleaver and channel coding structures are detailed in this study. OFDM system structure is simulated on the Rarleigh, Rician, AWGN channel models and its performance is evaluated.The LS, MMSE and LRMMSE algorithms used for channel estimation are compared. Key Words: OFDM, WiFi, WIMAX, ISI, LOS, NLOS, BER, LS, MMSE, LRMMSE
Channel estimation and performance analysis in orthogonal frequency division multiple access system
Keywords: İletişim Bilimleri; Elektrik ve Elektronik Mühendisliği